An approach to social mobilization for effective stakeholder participation in integrated water resource management in the Aral Sea Basin - Ul-Hassan, Mehmood; Yakubov, Murat (International Water Management Institute, 2004)
The framework reported here drives from the documentation and experiences gained under the SDC funded ?Integrated Water Resources Management in the Fergana Valley Project (IWRM-Fergana), which is implemented by the association comprising the International Water Management Institute (IWMI) and the Scientific Information Center of the Interstate Commission on Water Coordination (SIC-ICWC) of Central Asia.